Communication, Conflict, and Work Facilities: Determinants of Lecturer Work Commitment in Islamic Higher Education Institutions - Tubagus, Munir; Syarifuddin, Syarifuddin; Koderi, Koderi; Sabbar, Sabbar Dahham (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study investigates the influence of communication, conflict, and work facilities on lecturers' work commitment within Islamic higher education institutions. Previous research has emphasized the strategic role of effective communication and supportive work environments in enhancing organizational performance and employee engagement. However, limited attention has been given to understanding how these factors interact within the academic context of Indonesian Islamic universities. Using a quantitative research design, this study applied Structural Equation Modelling (SEM) with AMOS version 26 to analyze data from 310 permanent lecturers across four Islamic higher education institutions located in Manado, Makassar, Palu, and Ternate. The results reveal that communication has a significant and positive impact on lecturers' work commitment, indicating that open and effective interaction among academic members strengthens emotional attachment and professional responsibility. In contrast, conflict and work facilities show no significant influence, suggesting that interpersonal challenges and infrastructural conditions may play a less direct role in shaping commitment levels. These findings underscore the crucial role of internal communication in laying the groundwork for enhancing organizational loyalty and academic performance. Institutional leaders are advised to foster transparent, respectful, and participatory communication practices to sustain high levels of lecturer commitment and institutional productivity.